2009
DOI: 10.1128/iai.00759-09
|View full text |Cite
|
Sign up to set email alerts
|

Codependent and Independent Effects of Nitric Oxide-Mediated Suppression of PhoPQ andSalmonellaPathogenicity Island 2 on IntracellularSalmonella entericaSerovar Typhimurium Survival

Abstract: Here we show that the Salmonella enterica serovar Typhimurium PhoQ sensor kinase lessens the cytotoxicity of reactive nitrogen species (RNS) generated by inducible nitric oxide synthase (iNOS) in the innate response of mononuclear phagocytic cells. This observation is consistent with the expression patterns of PhoP-activated genes during moderate nitrosative stress in the innate host response. In contrast, RNS synthesized during high-NO fluxes of gamma interferon (IFN-␥)-activated macrophages repress PhoP-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 67 publications
3
15
0
3
Order By: Relevance
“…Because the SPI2 type III secretion system minimizes the contact of Salmonella phagosomes with vesicles harbouring NADPH oxidase or iNOS enzymatic complexes (Vazquez-Torres et al, 2000b;Gallois et al, 2001;Chakravortty et al, 2002;Suvarnapunya and Stein, 2005;Berger et al, 2010), the capacity of LMW thiols to preserve SPI2 transcription in Salmonella enduring moderate levels of nitrosative stress could indirectly boost the antioxidant and antinitrosative arsenal of this intracellular pathogen. Our previous work showed that nitrosative stress represses SsrB-and PhoP-dependent SPI2 transcription in Salmonella (McCollister et al, 2005;Bourret et al, 2009). Accordingly, LMW thiols could protect SsrB and PhoP signalling cascades from the inhibitory effects of RNS.…”
Section: Discussionmentioning
confidence: 97%
“…Because the SPI2 type III secretion system minimizes the contact of Salmonella phagosomes with vesicles harbouring NADPH oxidase or iNOS enzymatic complexes (Vazquez-Torres et al, 2000b;Gallois et al, 2001;Chakravortty et al, 2002;Suvarnapunya and Stein, 2005;Berger et al, 2010), the capacity of LMW thiols to preserve SPI2 transcription in Salmonella enduring moderate levels of nitrosative stress could indirectly boost the antioxidant and antinitrosative arsenal of this intracellular pathogen. Our previous work showed that nitrosative stress represses SsrB-and PhoP-dependent SPI2 transcription in Salmonella (McCollister et al, 2005;Bourret et al, 2009). Accordingly, LMW thiols could protect SsrB and PhoP signalling cascades from the inhibitory effects of RNS.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, iNOS-knockout mice were more susceptible to Salmonella infection, and macrophages from these animals displayed a decreased ability to kill intracellular Salmonella (Mastroeni et al, 2000;Vazquez-Torres et al, 2000a). Interestingly, it has been shown that RNS synthesized during high NO fluxes can repress the phoP-phoQ system responsible for survival of intracellular Salmonella (Bourret et al, 2009). Thus, the low expression levels of iNOS and subsequently of NO in p14 2/2 macrophages might favor the survival and replication of Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, most of these ATR-linked genes have been shown to regulate different virulence factors needed for colonization or survival within host cells (Rychlik & Barrow, 2005). Thus, the regulators Fur, PhoPQ and OmpR have been recently involved in the induction of genes from the Salmonella pathogenicity islands I and II, essential for the invasion of epithelial cells (Bourret et al, 2009;Ellermeier & Slauch, 2008;Fass & Groisman, 2009;Kim & Falkow, 2004;Lee et al, 2000). In fact, Perez et al (2010), studying the influence of acid adaptation on the survival of S. Typhimurium during intestinal infection of Rattus norvegicus, found that non-adapted microorganisms were observed in higher counts in feces than acid-adapted cells, while acid adapted microorganisms demonstrated higher counts in intestinal samples, suggesting a greater intestinal invasion capacity.…”
Section: Food Safety Implications Of S Typhimurium Atrmentioning
confidence: 99%